2017
DOI: 10.18632/oncotarget.18900
|View full text |Cite
|
Sign up to set email alerts
|

Role of nab-paclitaxel in metastatic breast cancer: a meta-analysis of randomized clinical trials

Abstract: Whether nab-paclitaxel and conventional taxanes are equally effective for metastatic breast cancer (MBC) remains unclear. We conducted meta-analysis of trials that compared nab-paclitaxel-based chemotherapy with solvent-based paclitaxel (sb-paclitaxel) and docetaxel-based chemotherapy. A literature search was performed to identify articles that compared nab-paclitaxel-based chemotherapy with sb-paclitaxel or docetaxel-based chemotherapy for MBC. Four randomized controlled trials (1,506 patients) were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
18
1
1
Order By: Relevance
“…There is no evidence that paclitaxel agents (solvent based or nanoparticle bound) are less effective than docetaxel; on the contrary, nab-paclitaxel demonstrated improved PFS compared with docetaxel in a prospective randomised trial [8]. Nanoparticle albumin-bound (nab)-paclitaxel appears to offer similar efficacy to docetaxel, with less frequent neutropenia but more frequent sensory neuropathy [9,10]. A single-arm study (N ¼ 51) evaluating weekly paclitaxel combined with trastuzumab and pertuzumab as first-or second-line therapy reported median PFS of 25.7 months and median OS of 33 months [11].…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that paclitaxel agents (solvent based or nanoparticle bound) are less effective than docetaxel; on the contrary, nab-paclitaxel demonstrated improved PFS compared with docetaxel in a prospective randomised trial [8]. Nanoparticle albumin-bound (nab)-paclitaxel appears to offer similar efficacy to docetaxel, with less frequent neutropenia but more frequent sensory neuropathy [9,10]. A single-arm study (N ¼ 51) evaluating weekly paclitaxel combined with trastuzumab and pertuzumab as first-or second-line therapy reported median PFS of 25.7 months and median OS of 33 months [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Arm A, G2 neurotoxicity was reported after a median of 6.5 cycles (range, 2-11), with G3 reported after a median of 6 cycles (range, 3-9). In contrast, G2 neurotoxicity was reported in Arm B after a median of 5 cycles (range, 1-11), with G3 reported after a median of 4.5 cycles (range, [3][4][5][6][7][8]. Severe AEs were reported in ten patients (13%) in each arm.…”
Section: Safetymentioning
confidence: 94%
“…However, close monitoring is required as treatment-induced side-effects, particularly neurotoxicity and fatigue, place older patients at risk of subsequent functional decline (FD) (3)(4)(5). Nanoparticle albumin-bound paclitaxel (nabpaclitaxel) does not require steroid premedication, and is associated with a lower rate of hypersensitivity reactions (6)(7)(8), thus representing an efficacious and safe alternative to solventbased taxanes. Additionally, recovery from nab-paclitaxel-induced neurotoxicity is reputedly shorter than with solvent-based taxanes (6,7), which may subsequently produce a reduction in negative functional impact.…”
Section: Introductionmentioning
confidence: 99%
“…treatment of metastatic breast cancer (MBC), and they concluded that nab-paclitaxel was associated with more frequent sensory neuropathy, but only equivalent survival and possibly higher overall response for only some specific subgroups 7 . They also cited that nab-paclitaxel chemotherapy was more expensive than conventional sb-taxane chemotherapy 7 .…”
mentioning
confidence: 99%
“…treatment of metastatic breast cancer (MBC), and they concluded that nab-paclitaxel was associated with more frequent sensory neuropathy, but only equivalent survival and possibly higher overall response for only some specific subgroups 7 . They also cited that nab-paclitaxel chemotherapy was more expensive than conventional sb-taxane chemotherapy 7 . The findings of Liu et al seemed to be affected largely by the phase III trial of Rugo et al In this trial, they administered bevacizumab (10 mg/kg, day1, day15), along with nab-paclitaxel (for the experimental arm) or sb-paclitaxel (for the control arm) to chemotherapy-naive MBC patients.…”
mentioning
confidence: 99%